Optimal Concentration Control for Direct Methanol Fuel Cells. Issue 8 (2015) - Zenith, Federico; Na, Youngseung; Krewer, Ulrike
Abstract: Two modifications to a reference direct methanol fuel-cell (DMFC) system are considered to improve methanol fuel utilisation. Fuel utilisation can be optimised by minimising the parasitic methanol crossover by manipulating methanol concentration in the fuel cells. Simulations of the two systems indicate that there is considerable potential to increase fuel utilisation for dynamic concentration control in DMFC systems subject to variable load.